2017
DOI: 10.1088/1748-3190/aa65db
|View full text |Cite
|
Sign up to set email alerts
|

Design and stable flight of a 21 g insect-like tailless flapping wing micro air vehicle with angular rates feedback control

Abstract: An insect-like tailless flapping wing micro air vehicle (FW-MAV) without feedback control eventually becomes unstable after takeoff. Flying an insect-like tailless FW-MAV is more challenging than flying a bird-like tailed FW-MAV, due to the difference in control principles. This work introduces the design and controlled flight of an insect-like tailless FW-MAV, named KUBeetle. A combination of four-bar linkage and pulley-string mechanisms was used to develop a lightweight flapping mechanism that could achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
136
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 78 publications
7
136
0
Order By: Relevance
“…a Delfly Nimble, b RoboBee X-wing with a flapping amplitude of 180°and wings clapped and flinged at the end of upstroke and downstroke. They measured the averaged lift of this model and found that the clap-and-fling effect leads to a lift augment by about 16% [23]. In summary, wing that could benefit from clap-and-fling effect in lift augment has been widely accepted, however, its effect on wing aerodynamic power consumption as well as power efficiency remains unclear and detailed investigation is still needed to design a micro four-wing FMAV for larger lift production.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…a Delfly Nimble, b RoboBee X-wing with a flapping amplitude of 180°and wings clapped and flinged at the end of upstroke and downstroke. They measured the averaged lift of this model and found that the clap-and-fling effect leads to a lift augment by about 16% [23]. In summary, wing that could benefit from clap-and-fling effect in lift augment has been widely accepted, however, its effect on wing aerodynamic power consumption as well as power efficiency remains unclear and detailed investigation is still needed to design a micro four-wing FMAV for larger lift production.…”
mentioning
confidence: 99%
“…Wing passive deformations beneficial for lift augment and power efficiency enhancement have also been discovered [17][18][19][20]. Then, various MAV prototypes using gear transmission, piezoelectric as well as electromagnetic drives were built, such as Robobee [21] of Harvard University, hummingbird [22] of AeroVironment Inc., KU Beetle [23] of Konkuk University, and Colibri [24] of ULB. After flying test of both vertical take-off and hovering flight, the dynamic stability of those bionic FMAVs has been further studied to guide flight control system design so as to finally achieve maneuvering flight.…”
mentioning
confidence: 99%
“…where I is the total moment of inertia about C and the various terms involved in the right-hand side are defined by equations (7)- (10). Notice that the added masses appear only in the inertia forces and not in the horizontal component of the thrust force.…”
Section: Rigid Body Dynamics Near Hoveringmentioning
confidence: 99%
“…The complex unsteady aerodynamic mechanisms generated by insects and humming birds in hovering flight have been gradually understood over the past decades. [1][2][3][4] More recently, the extreme miniaturization of avionics stimulated the engineering community to consider building robots mimicking the behavior of insects and birds, leading to impressive projects such as Delfly, 5 Harvard's Robobee, 6 Festo's robotic Seagull, 7 AeroVironment's Nano Hummingbird, 8 University of Texas A&M, 9 or Konkuk University in Korea, 10 to quote only a few. Beyond the mere curiosity of mimicking nature, it is believed that the ornithopters will one day outperform in agility the best quadcopters.…”
Section: Introductionmentioning
confidence: 99%
“…This is unmatched by man-made counterparts. Great progress has been made in recent years in the development of Flapping Wing Micro Air Vehicles (FWMAVs), among which Delfly [2], RoboBee [3], Nanohummingbird [4], KUBeetle [5], COLIBRI [6] and Purdue Hummingbird robot [7] have demonstrated successful takeoff and hovering.…”
Section: Introductionmentioning
confidence: 99%